(untitled) (Experimental biology, 2024)
Molybdenum is a key trace element for plants as it is an important component of the active center of several molybdenum containing enzymes. Molybdenum deficiency in young plants is characterized by chlorosis, leaf distortion, grayish coloration. The symptoms in old plants can be observed in young leaf tissues with typical lamina deformation, loss of the correct shape-whiplash tail and meristem necrosis. The soils in the Republic of Kazakhstan suffer from the molybdenum shortage, which makes plants more sensible to the abiotic and biotic stresses. This topic is relevant for the development of agriculture in the territory of the Republic of Kazakhstan. Tungsten as a chemical antagonist of molybdenum can replace molybdenum in the active center of molybdoenzymes making them inactive. Tungsten also has a toxic effect. The research results of this experimental work can be interpreted and replicated for economically significant agricultural crops such as peppers, potatoes, eggplant and tomato.